The metabolic endotoxemia and gut microbiota: research trajectories and hot trends across the centuries (1999–2024) - Jian, Enlin; Wang, Mengping; Zhang, Zhen; Heng, Yiwei; Zhang, Chengwei; Chen, Qing; Yu, Xiaoping; Zhu, Yanfeng; Cai, Peiling (Frontiers in Microbiology, 2025)
BackgroundMetabolic endotoxemia, characterized by chronic low-grade elevation of circulating bacterial endotoxins such as lipopolysaccharides derived from Gram-negative bacteria, has emerged as a central focus in metabolic disease research. Notably, emerging evidence highlights the pivotal role of gut microbiota in driving this condition, though critical knowledge gaps persist regarding the precise mechanisms mediated by gut microbiota-derived metabolites and their specific signaling pathways, as well as the development of individualized intervention strategies. To systematically map the evolving research landscape, this review employs bibliometric analysis to identify emerging trends and patterns in understanding the interplay between metabolic endotoxemia and gut microbial communities.Materials and methodsThis study employed a comprehensive bibliometric analysis of scholarly literature indexed in the Web of Science Core Collection (1900–2024) to investigate research patterns in metabolic endotoxemia and gut microbiota. Through multidimensional examination using VOSviewer, CiteSpace, the bibliometrix R package, and the online bibliometric analysis platform (https://bibliometric.com/), we systematically mapped research priorities, collaborative networks, and evolving frontiers in this interdisciplinary field. The methodology incorporated advanced visualization techniques and quantitative assessments to identify thematic clusters, institutional contributions, and knowledge diffusion pathways within the extant literature corpus.ResultsThis comprehensive global analysis, encompassing 1,585 relevant studies, demonstrates compelling evidence that China and USA collectively contribute over 50% of scientific output in this specialized research domain. Notably, academic investigations into metabolic endotoxemia and gut microbiota continue to maintain substantial research momentum. Current scholarly discourse prominently features five key thematic clusters: gut dysbiosis, intestinal barrier, risk, gut-liver axis, and short-chain fatty acids.ConclusionThis in-depth review systematically examines the evolving research landscape and emerging investigative priorities in metabolic endotoxemia and gut microbiota. It equips researchers with a comprehensive overview of key contributors in these specialized fields, including leading nations, institutions, academic journals, and potential collaborative networks. The analysis further delineates cutting-edge research frontiers and proposes strategic directions for future investigation, thereby serving as an invaluable resource for scholars navigating the complex interplay between metabolic endotoxemia and gut microbiota in the intestinal ecosystem.